The effect of advertisement image culture-advertised product culture congruency on perceived quality and attitude towards product in an ad - Tok, Choon Siang (2013)
As consumers are constantly bombarded by vast amounts of advertisements, they form different quality perceptions of products as well as attitudes toward advertised products. This study examines Advertisement Image Culture-Advertised Product Culture (AIC-APC) Congruency as an important variable which aids consumer process of attitude and quality perceptions formation. The study investigates the extent to which Perceived Quality mediates the relationship between AIC-APC Congruency and consumer Attitude Toward Product in the Ad (Apa). The mediation procedures advocated by Baron and Kenny (1986) were utilized for the mediation test. Findings confirmed the assertions of the study that (1) AIC-APC congruency has a positive impact on Apa, (2) consumers rely on AIC-APC congruency to form quality perceptions, and (3) Apa is influenced by perceived quality of product in an ad. Finally, results show that perceived quality fully mediates the relationship between AIC-APC congruency and Apa. These findings indicate that consumers rely on AIC-APC congruency as an extrinsic signalling cue when forming attitude toward product in the ad as well as quality perceptions of advertised product. In addition, this study contributes to the advertising congruency literature by integrating consumer perceptions and attitudes in a theoretical model and presents an entirely new dimension of on how consumers interpret ads and form product attitudes based on AIC-APC congruency. An important managerial implication to marketers is to help them develop more effective advertising strategies when introducing new products, leveraging on AIC-APC congruency to boost consumers’ quality perceptions and product attitudes.